2005
DOI: 10.1097/01.gim.0000151152.78092.ca
|View full text |Cite
|
Sign up to set email alerts
|

PON1 polymorphism, diabetes mellitus, obesity, and risk of myocardial infarction: Modifying effect of diabetes mellitus and obesity on the association between PON1 polymorphism and myocardial infarction

Abstract: Purpose: Previous studies on PON1 gene polymorphism and the risk of coronary atherosclerotic diseases have been inconsistent. This may be in part due to population difference in prevalence of high oxidative stress and its modifying effect on the association. Diabetes and obesity are two major risk factors of myocardial infarction (MI) and associated with high oxidative stress. We investigated the association between PON1 Q192R polymorphism and the risk of myocardial infarction (MI) and in particular, whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…On the other hand, a weak but significant association (OR=1.12 with 95% CI=1.07-1.16 for the 192 Arg allele) was found between the Gln192Arg and CAD, defined "of uncertain importance" by the authors. Meta-analysis results should be cautiously interpreted taking into account the high heterogeneity of studied populations and clinical outcomes; nevertheless, the studies that showed the greatest positive association between PON1 polymorphisms and vascular risk were those with high-risk populations, mainly in subjects with diabetes [20,24,28,29,32,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a weak but significant association (OR=1.12 with 95% CI=1.07-1.16 for the 192 Arg allele) was found between the Gln192Arg and CAD, defined "of uncertain importance" by the authors. Meta-analysis results should be cautiously interpreted taking into account the high heterogeneity of studied populations and clinical outcomes; nevertheless, the studies that showed the greatest positive association between PON1 polymorphisms and vascular risk were those with high-risk populations, mainly in subjects with diabetes [20,24,28,29,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…The HDL particles from 55 Met/Met and 192 Gln/Gln individuals have been demonstrated to be most effective in protecting LDL from oxidative modification [19]. The alleles less effective in protecting from oxidative stress, 55 Leu and the 192 Arg, have been associated with an increased risk of vascular disease in some clinical studies [20- 35], but not all [36][37][38][39][40][41][42][43][44][45][46][47][48][49]. A recent meta-analysis showed no significant association between 55 Leu allele and coronary heart disease, whereas a weak, but statistically significant increased risk (OR=1.12 with 95% CI=1.07-1.16) was found for the 192 Arg allele [50].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which the physiological and environmental factors as well as the lifestyle and food habits act on the state of OS are complex and influenced by genetic factors such as the polymorphism of genes coding for proteins having pro-oxidant activities (myeloperoxidase-MPO-, the receptor of the type 1 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 angiotensin) or antioxidant activities (Cu/ZnSOD, MnSOD, ecSOD, PON-1, GPX, etc.) [61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…However, another prospective study on 17,537 Dutch women showed that increasing PON1 activity increased the risk of CAD (van Himbergen et al 2008), thus contradicting the results of the earlier studies, and added further controversy to understanding of the association between PON1 activity and CAD. Despite all these controversies, there is accumulating evidence over the last decade that it plays an important role in atherogenesis and that low PON1 activity increases the risk of coronary atherosclerosis (Jarvik et Diabetic patients are at higher risk of developing CAD (Li et al 2005;Mackness et al 2006). To the best of our knowledge there is only one report on the association between PON1 activity and CAD in patients with type 2 diabetes (Poh and Muniandy, 2010).…”
Section: Discussionmentioning
confidence: 95%